AI-Assisted Scientific Writing Training for Undergraduate Students: A Community Engagement Program Using Qwen and Avidnote at Universitas Al Irsyad Cilacap - Teguh Iman Santoso (SOCIRCLE : Journal Of Social Community Services, 2026)
Artificial Intelligence has reshaped higher education and research practices, particularly in supporting students’ ability to plan, draft, and refine scientific articles. However, many undergraduate students still face difficulties in developing academic outlines, synthesizing literature, organizing arguments, applying scholarly writing conventions, and validating sources. This community engagement activity aimed to introduce AI-assisted scientific writing using Qwen and Avidnote to students in the Entrepreneurship and Digital Business Program at Universitas Al Irsyad Cilacap. The activity was conducted as an interactive online workshop on Saturday, April 18, 2026, through the Faculty of Economics and Business, involving approximately 50 undergraduate students. The workshop consisted of conceptual explanation, live demonstrations, hands-on practice, guided drafting, discussion, and reflective feedback. Since the activity did not include complete quantitative evaluation data, the results are reported descriptively based on workshop implementation, participant engagement, observed practice, and learning outputs. The results showed that participants were able to practice AI-assisted article outlining, literature synthesis, paragraph development, draft refinement, and source validation using Qwen and Avidnote. The main outputs of the activity included AI-assisted article outlines, preliminary academic writing drafts, revised paragraphs, and reflection notes on ethical AI use. The workshop also emphasized that AI-generated outputs must be reviewed critically, adjusted to academic writing standards, and supported by valid scholarly sources. This activity indicates that AI-assisted writing workshops can support undergraduate students’ academic literacy when combined with guided practice, source verification, and academic integrity awareness. Follow-up mentoring, AI writing clinics, and integration of responsible AI use into academic writing courses are recommended to strengthen students’ long-term scientific writing competence.